Optimizing the power and energy consumption of powered prosthetic ankles with series and parallel elasticity. (October 2017) - Verstraten, Tom; Geeroms, Joost; Mathijssen, Glenn; Convens, Bryan; Vanderborght, Bram; Lefeber, Dirk
Highlights: An optimization of parallel and series elastic elements in powered prosthetic ankles which takes the limitations of the drivetrain into account. We analyze the electrical power and energy consumption of the optimized designs. We discuss the effect of gear ratio and drivetrain inertia on the optimized elastic elements. The inertia of the motor and gearbox lead to unexpected power peaks in the swing phase. Results demonstrate the importance of selecting a motor at the beginning of the design process. Abstract: Several works have shown that series and parallel elasticity can reduce peak power and energy consumption in prosthetic ankles. Setting the right stiffness of the elastic elements is essential to unlock this potential. In this work, we perform a thorough optimization of series and parallel elastic elements for a prosthetic ankle driven by a geared DC motor. Through simulation, we study the effect of drivetrain limitations and compare different mechanical and electrical optimization objectives. The results highlight the importance of selecting a motor and gearbox in an early stage of the design process. Drivetrain inertia causes peaks in electrical power in the swing phase, which would go unnoticed in an optimization based solely on mechanical power. Furthermore, limitations of the drivetrain and controller reduce the range of applicable springs. This has a direct influence on the optimized spring stiffness values, which, as a result, are different from other works. Overall, the results suggest that, by integrating motor selection into the early stages of the design process, designs can be made lighter, more compact and more efficient.